Influence of different packaging structures on forced air pre-cooling effect of blueberry - WANG Da; YANG Xiangzheng; JIA Binguang; WU Maoyu (浙江大学学报. 农业与生命科学版, 2020)
In order to overcome the disadvantages of the large pressure loss, temperature unevenness and slow cooling rate, a packaging system which was suitable for the small diameter fruit of pre-cooling was discussed by using computational fluid dynamics (CFD) software. The mathematical models of four types of packaging systems were established, taking the current harvesting, pre-cooling and storage boxes of blueberry as the research objects to investigate the influence of height of trapezoidal hole on the pre-cooling effect of blueberry when the opening rate was constant. The results indicated that the change trend of pre-cooling time of the four types of packaging systems was box 1 ＞ box 2 ＞ box 4 ＞ box 3, and the pre-cooling time and the height of the trapezoidal hole showed the positive correlation; the change trend of pressure loss, unevenness and plot ratio were the same, all of which were box 4 ＞ box 3 ＞ box 2 ＞ box 1, and there was negative correlation between the pressure loss, unevenness, plot ratio and the height of the trapezoidal hole. The change rate of pre-cooling time, pressure loss, unevenness and plot ratio were 6.98%, 24.10%, 28.10% and 23.30%, respectively, when the trapezoidal height increased from 20 mm to 34 mm. In general, pre-cooling time, pressure loss, unevenness and plot ratio should be comprehensive considered when the packaging systems of blueberry are chosen. Box 3 or 4 should be opted, if highly cooling rate and plot ratio are carried out. Contrarily，box 1 or 2 are a better choice，if the operators want to decrease energy consumption and increase uniformity of blueberry on pre-cooling.